2022
DOI: 10.1149/10914.0041ecst
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic and Thermodynamic Properties of Ytterbium Chloride and Fluoride Complexes in Chloride Melts

Abstract: The electrochemical behavior of ytterbium in NaCl-KCl, KCl and CsCl melts was studied in the temperature range 973-1173 K by different electrochemical methods. The diffusion coefficients (D) of Yb(III) and Yb(II) were determined by linear sweep voltammetry, chronopotentiometry and chronoamperometry methods. The standard rate constants of charge transfer (k s) for the Yb(III)/Yb(II) redox couple were calculated on the basis of cyclic voltammetry data using Nicholson’s equation. The formal redo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…In our previous works 44,46,53,54 we determined diffusion coefficients (D) and diffusion activation energies (U) for molten systems NaCl-KCl-LnCl 3 (Ln -Eu, Sm, Yb). Let us consider how these values depend on the nature of lanthanide (Ln) cation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In our previous works 44,46,53,54 we determined diffusion coefficients (D) and diffusion activation energies (U) for molten systems NaCl-KCl-LnCl 3 (Ln -Eu, Sm, Yb). Let us consider how these values depend on the nature of lanthanide (Ln) cation.…”
Section: Resultsmentioning
confidence: 99%
“…The standard rate constants of charge transfer were determined early in the NaCl-KCl melt by cyclic voltammetry for the Eu(III)/Eu(II), 44,46 Sm(III)/Sm(II) 53 and Yb(III)/Yb(II) 54 redox couples. The following series of k s for the Ln(III)/Ln(II) redox couples have been established: k s (Nd) > k s (Sm) > k s (Eu) > k s (Yb).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using values of the ψ T function, obtained from Eqs. 9 and, 10 in conjunction with expression [8] allows to calculate the standard rate constants of charge transfer. The influence of the second coordination sphere and temperature on the standard rate constants of the electrode reaction [1] is presented in Table IV.…”
Section: Resultsmentioning
confidence: 99%
“…In pyrochemical processes chlorides of lanthanides are usually diluted in a molten salt medium and our works showed that the electrochemical transient techniques are not only a powerful tool for studying electrode kinetics, but also an effective method for the determination of thermodynamic properties. [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] The standard redox potentials of the Yb(III)/Yb(II) redox couple relative to the Pt(II)/Pt electrode in the LiCl-KCl melt have been measured at different temperatures. 23 Preliminary results on the diffusion coefficients (D) for Yb(III) and Yb(II) were determined by cyclic voltammetry, chronoamperometry and chronopotentiometry in KCl, CsCl, and the equimolar NaCl-KCl melts.…”
mentioning
confidence: 99%